The costs of social benefits in temporary employment - Mędrala, Małgorzata (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The aim of the article is to analyze the distribution of social benefits costs in temporary employment. The author points out that some of the social benefits typical for traditional employment have been completely excluded in temporary employment (severance payments for termination for reasons not related to employees), and the method of calculation of some cash benefits (holiday pay, equivalent for annual leave) has been modified for the purposes of temporary employment. To a large extent, the social burden of employment is transferred by the legislator to the temporary employment agency. Such solutions are justified by the short duration and subsidiarity of temporary employment as compared to traditional employment. The doubts are raised by the lack of access to benefits from the company’s social benefit fund for temporary employees on the same terms as ordinary employees of the user employer.